ANALISIS HARGA POKOK PRODUKSI NOVY HEADLAMP CUSTOM PADA PASAR KOTA TENGGARONG - Puspita Sari, Eka; Dewi, Septira; Aryani, Farida (I-Con Media, 2025)
This research aims to analyze the cost of production (HPP) of Novy Headlamp Custom products marketed in Teenggarong City. The method used in this research is quantitative by collecting primary and secondary data. Primary data was obtained through direct interviews with business owners and observations of production processes in the field, while secondary data was obtained from financial reports and relevant production documents. The cost components analyzed include raw material costs, labor costs, and production overhead costs. The research results show that raw material costs are the largest component in the COGS structure, followed by direct labor costs and overhead costs. Based on the analysis carried out, the HPP per unit for the Novy Headlamp Custom is Rp. 500,000. The selling price is then determined by considering the desired profit margin and market conditions in Tenggarong City. By knowing the HPP in detail, Novy Headlamp Custom can determine a pricing strategy that is more effective and competitive in the local market. The study also provides recommendations for improving production efficiency and reducing costs without compromising product quality. It is hoped that this analysis can become a reference for other small and medium businesses in managing their HPP.